A Driftwood‐Based Record of Arctic Sea Ice During the Last 500 Years From Northern Svalbard Reveals Sea Ice Dynamics in the Arctic Ocean and Arctic Peripheral Seas. Issue 10 (4th October 2021) - Hole, Georgia M.; Rawson, Thomas; Farnsworth, Wesley R.; Schomacker, Anders; Ingólfsson, Ólafur; Macias‐Fauria, Marc
Abstract: We present a 500‐year history of naturally felled driftwood incursion to northern Svalbard, directly reflecting regional sea ice conditions and Arctic Ocean circulation. Provenance and age determinations by dendrochronology and wood anatomy provide insights into Arctic Ocean currents and climatic conditions at a fine spatial resolution, as crossdating with reference chronologies from the circum‐Arctic boreal forests enables determination of the watershed the driftwood originated from. Sample crossdating may result in a wide range of matches across the pan‐boreal region, which may be biased toward regions covered by the reference chronologies. Our study considers alternate approaches to selecting probable origin sites, by weighting scores via reference chronology span and visualizing results through spatiotemporal density plots, as opposed to more basic ranking systems. As our samples come from naturally felled trees (not logged or both), the relative proportions of different provenances are used to infer past ocean current dominance. Our record indicates centennial‐to decadal‐scale shifts in source regions for driftwood incursion to Svalbard, aligning with Late Holocene high variability and high frequency shifts in the Transpolar Drift and Beaufort Gyre strengths and associated ﬂuctuating climate conditions. Driftwood occurrence and provenance also track the northward ice formation shift in peripheral Arctic seas in the past century. A distinct decrease in driftwood incursion during the last 30 years matches the observed decline in pan‐Arctic sea ice extent in recent decades. Our new approach successfully employs driftwood as a proxy for Arctic Ocean surface circulation and sea ice dynamics. Plain Language Summary: We present a 500‐year history of driftwood arriving to the shorelines of northern Svalbard. Driftwood in the Arctic results from dying trees entering the large rivers that drain the circum‐Arctic land masses, which upon flowing into the Arctic Ocean can become locked up in forming sea ice. This enables the wood to travel across the Arctic Ocean without sinking, making it an invaluable proxy for sea ice extent by recording variations in Arctic Ocean surface currents (and therefore sea ice drift) and ice cover. With comparison of tree ring width (TRW) measurements of these driftwood samples to TRW series from trees throughout the boreal forests, we can determine the region each sample came from. We can thus approximate its likely trajectory across the Arctic Ocean. Arctic sea ice is rapidly declining in extent and thickness, with impacts on local and global climatic and ecological conditions. Knowledge of past changes is needed to place this modern trend within a broader context to aid future predictions for Arctic sea ice. Our record matches the observational record of Arctic Ocean surface circulation patterns and climate conditions, supporting the use of driftwood as a proxy for Arctic Ocean surface current and sea ice dynamics. Key Points: We present a novel approach to utilizing naturally felled driftwood as a proxy for Arctic Ocean surface circulation and sea ice dynamics A 500‐year record of driftwood incursion to Svalbard reflects centennial to decadal variability in surface circulation and sea ice extent A distinct decrease in driftwood from all provenances in the last 30 years matches the observed decline in pan‐Arctic sea ice extent